Towards a Model of Leader Character Development: Insights From Anatomy and Music Therapy. (August 2021) - Crossan, Mary; Ellis, Cassandra; Crossan, Corey
Leader character has emerged as a critical foundation for leadership. In spite of the view that leader character can be developed, there has been limited holistic attention to what it takes to develop character. Character requires conscious development, and that conscious development not only requires an understanding of what character is, but how the anatomy of character enables and inhibits character development and expression. By anatomy, we refer to the four underlying anatomical systems—physiology, affect, behavior, and cognition (PABC)—that function independently, and in an interrelated manner, to support the development of character. For illustration, we offer the practice of listening to music as a means to develop character, highlighting the links between the PABC systems and character development.